The Effect of Learning Orientation and Digitalization of MSMES on the Implementation of MSME Internationalization - Iva Chandraningtyas; Sudarmiatin; Imam Mukhlis (PT Inovasi Pratama Internasional, 2022)
The purpose of this study was to examine the relationship between the variables of learning orientation, the digitization of SMEs and the implementation of the internationalization of SMEs. This research uses quantitative research. Data were collected from 82 respondents using a survey. Respondents of this study were SMEs engaged in handicrafts and accessories. The SEM_PLS data analysis technique uses the SMART-PLS application. The results of the hypothesis test show that (1) there is a significant effect of the digitization of SMEs on the implementation of the internationalization of SMEs. (2) There is a significant influence of the learning orientation variable on the digitization of MSMEs. (3) There is no significant effect of learning orientation variable on the implementation of MSME internationalization.